Genome-Wide Profiling of the Toxic Effect of Bortezomib on Human Esophageal Carcinoma Epithelial Cells. (19th July 2019) - Ao, Nannan; Dai, Yingchu; Chen, Qianping; Feng, Yang; Yu, Jingping; Wang, Chang; Liu, Fenju; Li, Ming; Liu, Geng
Objectives: Bortezomib has been widely used to treat multiple myeloma and other hematological malignancies. However, not much is known about its effect on solid tumors. The aim of this study was to study the effect of Bortezomib on human esophageal cancer cell lines and investigate the potential target pathways. Methods: Two human esophageal cancer cell lines, TE-1 and KYSE-150, were used in this study. Cell viability, cell cycle distribution, and apoptosis after Bortezomib treatment was detected by Cell Counting Kit-8, flow cytometry, and Annexin V/propidium iodide staining, respectively. The genes targeted by Bortezomib were analyzed at the messenger RNA level by microarray chips and quantitative real-time polymerase chain reaction. Results: The proliferation of human esophageal cancer cell lines was inhibited by Bortezomib in a dose- and time-dependent manner. Bortezomib treatment led to G2 /M arrest and apoptosis. Microarray chips revealed multiple signaling pathways targeted by Bortezomib, including proteasome, endoplasmic reticulum, Wnt-, and calcium-mediated pathway. The expression patterns of 4 representative genes UBD, CUL3, HDAC6, and GADD45A were verified by quantitative real-time polymerase chain reaction and showed consistency with the microarray assay. Conclusion: Bortezomib could suppress cell viability, cause G2 /M arrest, and induce apoptosis in human esophageal cancer cells, with possible targets including UBD, CUL3, HDAC6, and GADD45A.